Dermatitis Kontak Akibat Kerja pada Pengrajin Batik di Kecamatan Pelayangan Kota Jambi - Abul Ainin Hapis; Putri Sahara Harahap; Ahmad Husaini; Sugiarto Sugiarto; Fitriani Fitriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Dermatitis in batik workers is a common problem that often occurs due to exposure to chemicals and dyes in the batik production process. Batik workers who are directly exposed to these materials are susceptible to skin irritation or even allergic reactions. Long-term exposure to textile dyes, binders, and solvents can cause rashes, redness, itching, swelling, and scaly skin. The aim of this research was to determine the characteristics of DKAK among batik craftsmen workers in Pelayangan District, Jambi City. This research method is a cross sectional design research. The sampling technique was purposive sampling with a total of 40 respondents. Data was obtained by interviews and filling out questionnaires as well as examinations assisted by community health center people. The results of this study showed that there were two risk factors that were related in this study, namely length of exposure (p = 0.001). The most common clinical characteristics based on subjective symptoms are itching, objective symptoms are redness, and a predilection for the fingers and toes. The most common causes of irritants and allergens are synthetic dyes and wax. Exogenous and endogenous risk factors showed that the majority of respondents had no history of atopic eczema, age and skin anatomical condition. Conclusion: From these data there is a relationship between the factors of length of exposure and the incidence of DKAK in batik craftsmen in Pelayangan District, Jambi City.